2020
DOI: 10.1111/ceo.13846
|View full text |Cite
|
Sign up to set email alerts
|

Retinal microvasculature impairment in patients with congenital heart disease investigated by optical coherence tomography angiography

Abstract: Importance: A high prevalence of retinal abnormalities have been reported in congenital heart disease (CHD), but quantitative analysis of retinal vasculature is scarce. Optical coherence tomography angiography (OCTA) is a noninvasive method to quantitatively assess the retinal microvasculature. Background: To investigate the retinal microvasculature changes in CHD patients by using OCTA. Design: Cross-sectional study. Participants: A total of 158 participants including 57 cyanotic CHD (CCHD) patients, 60 acyan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 46 publications
0
11
0
2
Order By: Relevance
“…Therefore, retina is highly sensitive to hypoperfusion and hypoxia. It is found that the retinal VD is decreased in hypertension (Lee et al, 2019 ), coronary heart disease (Wang et al, 2019 ), congenital heart disease (Li et al, 2020 ), obstructive sleep apnea syndrome (Moyal et al, 2018 ), etc. Similarly, in the current study, we also observed a significantly reduced retinal VD in patients with stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, retina is highly sensitive to hypoperfusion and hypoxia. It is found that the retinal VD is decreased in hypertension (Lee et al, 2019 ), coronary heart disease (Wang et al, 2019 ), congenital heart disease (Li et al, 2020 ), obstructive sleep apnea syndrome (Moyal et al, 2018 ), etc. Similarly, in the current study, we also observed a significantly reduced retinal VD in patients with stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a decrease in wholeVD, foveaVD, and parafovealVD in the choroid capillaries was noted. In contrast, Li et al [ 45 ] analyzed VD in 117 patients with congenital heart disease (CD); 60 of them had acyanotic congenital heart disease (ACD), and 57 had cyanotic congenital heart disease (CCD). The authors noted a significant difference in vascular density: wholeVD ( p = 0.010) and perifovealVD ( p = 0.004) in SP in CCD patients compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this current study—that cardiovascular disease can lower vascular density—are in keeping with the findings of the above-referenced studies conducted earlier. It is believed that peripheral vasoconstriction in response to low cardiac output is the pathophysiological mechanism that triggers this outcome [ 39 , 43 , 45 ]. Almeida–Freitas et al [ 47 ] recorded higher resistance index and lower diastolic velocity in the ocular arteries of patients with low LVEF.…”
Section: Discussionmentioning
confidence: 99%
“…Given its excellent repeatability and reproducibility, OCTA has been widely used in clinical practice for monitoring microvascular function in hypertension (11), diabetes (12), and so on (13). In our previous study, a significant impairment of retinal microvasculature was found in the OCTA imaging of CHD patients (14). As for the alteration of postoperative retinal microvasculature, although it has been investigated in patients undergoing coronary artery bypass or valve replacement with CPB (15)(16)(17)(18), there is little evidence regarding patients undergoing congenital cardiac surgery.…”
Section: Introductionmentioning
confidence: 88%